MODERASI KEPEMILIKAN INSTITUSIONAL DALAM ANALISIS FAKTOR YANG MEMPENGARUHI EARNINGS MANAGEMENT - Richard Richard; Vidyarto Nugroho (Jurnal Paradigma Akuntansi, 2023)
This study aims to obtain empirical evidence regarding the effect of Firm Size, Leverage, Firm Age, Profitability, Audit Quality and institutional ownership on Earnings Management in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. There are 55 manufacturing companies selected as samples by purposive sampling method. Data were analyzed using multiple linear regression also Moderated Regression Analysis and processed with Eviews 12. The partial tests show significant positive effect of Leverage and Profitability on Earnings Management. The Moderation test shows that institutional ownership significantly moderate relationship of Size and Leverage on Earnings Management, but does not moderate relationship of Profitability and Earnings Management.